PERBANDINGAN GEOSTATISTIK METODE KRIGING DAN CO-KRIGING MENGGUNAKAN ESTIMASI POINT KRIGING - Arief Pambudi Nugraha (Retii, 2020)
This study aims to determine a variogram model with kriging and co-kriging with point kriging and point co-kriging estimation based on linear, exponential, spherical, gaussian variogram models and in isotropic and anisotropic orientations. The research method includes assay analysis of 132 data with the primary variable (Ur) having 24 data and the secondary variable (C) having 126 data. Data processing was done by looking for a model for each method in isotropic and anisotropic orientations. The determination of the model used cross validation by looking at the regression parameters R2, SE, and SE prediction. The results obtained are the kriging method, the best model is the spherical and the co-kriging method is the exponential model. From the comparison of the two methods, the isotropic orientation is better than anisotropic in terms of error and the results of the co-kriging method have a better estimate than kriging.